Komodifikasi Tubuh Perempuan di Instagram (Analisis Wacana pada Endorser Perempuan di Jember) - Al-Hadi, Robith Abdillah; Hidayat, Nurul (e-Sospol, 2017)
Abstract The research looked at the commodification of female body in Instagram. Commodification happened to parts of female body are used to gain the exchange rate. In this research, researcher saw a discourse on female endorser in Instagram. Hence, the researcher used the logic of commodification of Karl Marx, symbolic violence of Pierre Bourdieu, and discourse analysis method to analyze how the commodification of female body in Instagram is. The used informant determination method was snowball. The result of this research concluded that women in Instagram be commercialize by becoming themselves as an Endorser. The happened commodificationwas distinguished by categorization. Commodification on the face and hand occurred at endorser who wear veil with the product provision, but for the endorser who did not use veil, commoditization occurred on the entire body. On the other hand, endorser in terms of consciousness had two varieties where endorser who was aware that she was being commercialized. There was also an endorser who was not aware of and had their own ideals